2001
DOI: 10.1523/jneurosci.21-15-05670.2001
|View full text |Cite
|
Sign up to set email alerts
|

P2X3Knock-Out Mice Reveal a Major Sensory Role for Urothelially Released ATP

Abstract: The present study explores the possible involvement of a purinergic mechanism in mechanosensory transduction in the bladder using P2X(3) receptor knock-out (P2X(3)-/-) and wild-type control (P2X(3)+/+) mice. Immunohistochemistry revealed abundant nerve fibers in a suburothelial plexus in the mouse bladder that are immunoreactive to anti-P2X(3). P2X(3)-positive staining was completely absent in the subepithelial plexus of the P2X(3)-/- mice, whereas staining for calcitonin gene-related peptide and vanilloid rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
400
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 431 publications
(419 citation statements)
references
References 29 publications
11
400
0
4
Order By: Relevance
“…The altered P2X receptor expression accounts for greater current density in response to purinergic agonists, and likely contributes to the slowed desensitization kinetics of the slow desensitizing current after bladder inflammation. Considering the reported mechanosensory role for homomeric P2X 3 and P2X 2 and heteromeric P2X 2/3 receptors (Cockayne et al 2000(Cockayne et al , 2005Rong et al 2002;Vlaskovska et al 2001), and the increased urothelial release of ATP during inflammation (Sun et al 2001), the present findings suggest that the altered expression of P2X receptors contributes to the enhanced responses of bladder neurons during cystitis.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The altered P2X receptor expression accounts for greater current density in response to purinergic agonists, and likely contributes to the slowed desensitization kinetics of the slow desensitizing current after bladder inflammation. Considering the reported mechanosensory role for homomeric P2X 3 and P2X 2 and heteromeric P2X 2/3 receptors (Cockayne et al 2000(Cockayne et al , 2005Rong et al 2002;Vlaskovska et al 2001), and the increased urothelial release of ATP during inflammation (Sun et al 2001), the present findings suggest that the altered expression of P2X receptors contributes to the enhanced responses of bladder neurons during cystitis.…”
Section: Discussionsupporting
confidence: 52%
“…IC is associated with an increased release of adenosine triphosphate (ATP) from bladder urothelial cells (Sun et al 2001) and ATP is also released from bladder urothelium in response to stretch or bladder distension (Ferguson et al 1997;Vlaskovska et al 2001). Importantly, interactions between the urothelium and bladder nerve terminals are thought to regulate micturition and nociception (Andersson 2002;Kirkemo et al 1997;Meen et al 2001;Ness et al 2005;Tubaro 2004;Vlaskovska et al 2001), and ATP and P2X receptors have been implicated in bladder nociception (Ford et al 2006;Rapp et al 2005). For example, both P2X 2 and P2X 3 receptor knockout mice exhibit bladder hyporeflexia (Cockayne et al 2000(Cockayne et al , 2005 and recordings from bladder primary afferent fibers show attenuated responses to mechanical bladder stimulation (Vlaskovska et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both pre-and post-junctional mechanisms caused the maturation of fast purinergic junctional transmission of the longitudinal muscle of the mouse vas deferens between 21 and 42 days postnatal [239]. By analogy with the release of transmitters from endothelial cells lining blood vessels (see [61]) and urothelial cells in bladder and ureter [212,421], it was shown that prostaglandin E 2 was released from epithelial cells of the rat vas deferens in response to neurally released ATP acting via P2Y receptors to mediate neurogenic contractions [353].…”
Section: Vas Deferensmentioning
confidence: 99%
“…The tachykinins neurokinin A, neurokinin B, and substance P, which are present within sensory nerves and locally released by a number of physical and chemical stimuli, 23,24 have many important biological actions, including C fiber activation. Other animal studies have shown that transient receptor potential vanilloid 1 (TRPV1) 18,25 and P2X3 purine receptors 26 also have important roles in bladder overactivity. Therefore, we sought to determine if Gosha-jinki-gan reduces these transmitter proteins and sensory receptors as one of the mechanisms to mediate acetic acid-induced C fiber activation.…”
Section: Introductionmentioning
confidence: 99%